Vertical spin transport in semiconductor heterostructures: Структура и свойства полупроводников с переходными элементами - Sankowski, P.; Kacman, P.; Majewski, J.A.; Dietl, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The Landauer—Büttiker formalism combined with the tight-binding transfer matrix method is employed to model vertical coherent spin transport within magnetization modulated semiconductor heterostructures based on GaAs. This formalism provides excellent physical description of recent experiments concerning the high tunneling magnetoresistance (TMR) in (Ga,Mn)As-based trilayers and highly polarized spin injection in p-(Ga,Mn)As/n-GaAs Zener diode. For both the TMR and the Zener spin current polarization, the calculated values compare well with those observed in the experiments and the formalism reproduces the strong decrease of the observed effects with external bias. We ascribe this decrease to the band structure effects. The role played in the spin dependent tunneling by carrier concentration and magnetic ion content is also studied.